Comparison of Post Dural Puncture Headache Among Patients Administrated Spinal Anesthesia with 25 Gauge and 27 Gauge Needles Undergoing Elective Cesarean Section - Tahir, Syeda Amna; Fakhr, Fakhra; Mahmood, Raja Azhar; Rehman, Wajeeh Ur (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the outcome of 25 Gauge and 27 Gauge needles in terms of Post Dural Puncture Headache in patients undergoing spinal anesthesia at Gynae Surgical Wards. Study Design: Quasi experimental study. Place and Duration of Study: The study was conducted at the Gynae Surgical Wards of the Shalamar Hospital in Lahore, Pakistan from Sep 2022 to Apr 2023. Methodology: 58 patients who met the study’s inclusion requirements were recruited through non-probability, convenient sampling. They were split into two groups 29 patients in Group-A and 59 patients in Group-B. After obtaining informed consent, patients in Group-A received spinal anesthesia with a 25-gauge needle, whereas Group-B received spinal anesthesia with a 27-gauge needle. The data was collected using Proforma. At 24, 48, and 72 hours following the procedure, Post Dural Puncture Headache was assessed and data was analyzed using SPSS. Results: The mean age of the subjects in Group-A was 26.21±3.016 years and the mean age of subjects in Group-B was 25.07±3.722 years. 21 patients out of 29 in Group-A (72.4%) developed PDPH. While only 9 Patients out of 29(31%) developed PDPH in Group-B. There is an association between needle gauge and headache (p-value 0.002). Conclusion: The use of a 27G needle for administering spinal anesthesia should be preferred over a 25G needle, as the frequency of PDPH was found to be lower with the former.